Analisis Penilaian dan Pengendalian Resiko Pada Perawatan Jalan Rel dengan Metode HIRARC di PT KAI (PERSERO) Divisi Regional III Palembang - Alfauzu Alfauzu; Muhammad Firdaus; Herri Purwanto (Institut Teknologi Garut, 2025)
The purpose of this study is to assess the level of work accident risk that exists and determine the possibility of failure in operational railroad maintenance work as well as evaluate the way railroad maintenance officers work by creating a risk control plan. The HIRARC (Hazard Identification, Risk Assessment and Risk Control) method was chosen because it provides a systematic approach to identifying hazards, assessing risks and controlling potential hazards in the work environment. The research covers five potential dangers that could endanger the safety of officers when carrying out rail maintenance work, including the risk of respiratory problems, peeling of hands, eyes exposed to welding fire, sprained feet and hands and eye irritation and recommendations for mitigation of these five risks include: using innovative rocking ballast machine tools, using cotton gloves or rubber gloves, using dust goggles, using safety masks, using safety helmets and safety shoes.